Estudio de prefactibilidad para la instalación de una planta de producción de barras de cereal a base de granola con arándanos (Vaccinium corymbosum) y fresas (Fragaria) deshidratados - Li Santos, Alicia Jiu Yen (2020)
The granola bar with dried strawberries and blueberries is a healthy snack for human consumption that provides energy, protein, vitamins, fiber and iron. In view of the fact that in society there is a high percentage of people who tend to consume unhealthy snacks as part of their diet, we seek to offer the market a healthy product. Therefore, in the present research project a prefeasibility study has been carried out to determine the market, technical, economic and financial viability for the installation of a granola bar with dried blueberries and strawberries manufacturing plant. The target market for this project are people who belong to the socioeconomic level B in the Lima Metropolitan area. The demand for the first year is 80.327,26 kg with an annual increase of 4%. The product is sold in a box of 6 units at a value of S/ 8.95 and is distributed to supermarkets and self-services. Regarding the analysis of the location of the manufacturing plant, it is located in the district of Lurin, in the region of Lima, due to the low cost of the land compared to the other proposals evaluated and its proximity to the target market. As far as the plant size is concerned, it is 628.648,00 boxes of granola bar and it is limited by the market size. That is, resources and technology are sufficient to carry out the project. A total investment of S/ 1,703,043 is required so that the operation of the project can be carried out. As a result of the analysis of the economic and financial indicators, the NPVE and NPVF are S/ 1,549,494 and S/ 1,645,367, respectively. Likewise, the IRRE (47%) and the IRRF (64%) are higher than the COK.